(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Firdaus N, Supriatna, Supriatna J. 2022. Ecosystem services research trends in Indonesia: a bibliometric analysis. Biodiversitas 23: 1105-1117. Among the world’s mega-biodiversity countries in the tropics, Indonesia has experienced the most severe deforestation in recent decades. It is alarming that the rate is potentially disrupting the future provision of ecosystem services. On the other hand, there is a paucity of research on ecosystem services in Indonesia, and its current state is unknown. This study provided an overview of ecosystem services research trends in Indonesia from 1998 to 2020 using bibliometric and science mapping analysis of 298 published works from the Scopus database. Since 2013, publications on the topic have increased and grown exponentially, with environmental science dominating the subjects, followed by agriculture and biology, and the social sciences. Biodiversitas and Ecosystem Services are the most prolific journals for publishing results, while Science and Ecological Economics have the most citations. Being the most productive in publications, Indonesia and the United States are also engaged the most in research collaborations. Ecosystem services research in Indonesia is closely linked to biodiversity, deforestation, and oil palm. Furthermore, oil palm, sustainability, and land-use change are promising topics to address in the coming years. This study suggests that the dynamics of ecosystem services research in Indonesia call for further developments in improving the quality of impactful research through interdisciplinary approaches, international collaboration, and the engagement of diverse stakeholders and policy-makers related to the field, to increase the benefits of sustainable ecosystem services in the future.